Pengaruh Gaya Kepemimpinan dan Stres Kerja Terhadap Turn Over Karyawan Mahasiswa/Mahasiswi di Daerah Pamulang - Muhammad Febrian; Chelvin Rickot; Vira Nofiyansyah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The purpose of this study was to analyze the effect of leadership style and work stress on student employee trun over in Pamulang area. The variables used in this study are Leadership Style and Job Stress on employee truncation. Methods This research uses quantitative methods. The data used in this study were data obtained directly by the researcher by distributing questionnaires directly to female/student employees in the Pamulang area. The population and sample in this study were female/student employees in the Pamulang area of ​​111 female/student employees. The data analysis technique used is t test, f test and coefficient of determination test, using SPSS 24 software. The results of this study indicate that (1) The influence of leadership style (x1) has no effect on turnover. (2) The influence of the work stress variable (x2) has an influence on turnover. So the results of this study indicate that the influence of variables that have a very large and significant influence is work stress which causes frequent student employee turn over at their workplaces in the Pamulang area.